The effectiveness of graded motor imagery for reducing phantom limb pain and disability in amputees - Limakatso, Katleho Maxwell (Adolescent Health Research Institute, 2019)
Introduction Phantom limb pain (PLP) is described as painful sensations felt in the missing portion of an amputated limb. PLP occurs in up to 85% of amputees, making it the most common painful condition secondary to amputation. PLP interferes with sleep, mobility, and work, general activities of daily living and enjoyment of life. Current pharmacological and non-pharmacological interventions have shown limited efficacy for reducing PLP, perhaps because they do not effectively target the mechanisms that have been proposed to underlie PLP in people who have undergone amputations. Graded motor imagery (GMI) is a cortical mechanisms-based intervention which aims to reduce PLP using a graded sequence of strategies including left/right judgements, imagined movements and mirror therapy. The aim of this thesis was to investigate whether the GMI programme is effective for reducing PLP and disability in people who have undergone amputations. Methods A single blinded randomised controlled trial was conducted at Somerset, Khayelitsha and Victoria hospitals in Cape Town, South Africa. The experimental group underwent a 6-week GMI programme where each phase was carried out for two weeks, during which the patient received treatment for 30 minutes on two separate days of the first week (at least one day apart) and continued with a structured home-exercise programme during the first week until the end of the second week. The control group continued with routine care. Data on the outcomes- PLP severity, pain interference with function and health-related quality of life were collected at baseline, 6 weeks and 3 months by a blinded outcome assessor. Results The study recruited 21 participants from which 11 and 10 were randomly allocated to the experimental and control groups respectively. Within group analysis showed that participants in both the experimental and control groups had improved pain severity scores immediately after treatment and at 3-month follow-up. The between-group analysis showed that the experimental group had significantly greater improvements in pain immediately after treatment (p=0.02). However, there was no difference between groups at 3-months follow-up (p=0.14). To explore clinically meaningful improvements in pain, the Number Needed to Treat (NNT) were calculated using a cut-off of 3 points on a 0-10 scale. The NNT were 2 [95% CI: 1.1 – 6.5] and 3 [95% CI: 1.9 – 7.1] immediately after treatment and at 3-months follow-up respectively. For pain interference with function, within group analysis showed that participants in the experimental group had significant improvements immediately after treatment and at 3-month follow-up. The between-group analysis showed that the experimental group had significantly greater improvements in pain interference with function immediately after treatment (p=0.007) and at 3- month follow-up (p=0.02). The NNT were 1.4 [95% CI: 1 – 1.8] and 1.9 [95% CI: 1.1 – 6.5] immediately after treatment and at 3-months follow-up respectively. For disability, the experimental group had significantly fewer problems with mobility than the control group at 3 months (χ2 = 9.8; p= 0.04). Conclusion The results of the current study provide support for the use of GMI to treat PLP based on the proposition that PLP is driven by cortical mechanisms and that GMI effectively targets these mechanisms. On the basis of the significant pain reduction within the GMI group, the lack of serious adverse effects, and the ease of application, GMI may be a viable treatment for treating PLP in people who have undergone amputations. While more studies using rigorous methodology, including sham treatment, larger sample sizes and a more generalisable sample, are required, the efficacy of GMI coupled with its affordability and low risk, suggest that it is applicable in a resource-constrained primary health setting in South Africa.